Implementation of supervision techniques: A literature study - Muhimatul Kibtiyah; Deny Heryanto (Balai Diklat Keagamaan Ambon, 2022)
Academic supervision is the activity of guiding professionally by a supervisor/principal to the teacher so that the supervised party, in this case the teacher is able to carry out teaching tasks better. Given the importance of supervision, it is important for supervisors to know the techniques in supervision so that the objectives of supervision can be achieved. The purpose of this study is to determine the kinds of supervision techniques that can be carried out by a supervisor. This research is a literature study research by reviewing 16 articles on supervision techniques both individually and in groups. The result of this research is that various supervision techniques, both individual supervision techniques and group supervision techniques have been applied by supervisors.